To Assess the Satisfaction and its Influencing Factors with Online Teaching and Learning Activities during COVID-19 Pandemic among Nursing Students - Sharma, Jyoti; Bhagat, Anu (International Journal of Nursing Research, 2023)
Background of Study: COVID-19 pandemic has forced universities across the world to suspend physical classroom and shift to online classes. To cover up the loss on education system, online teaching and learning activities have been started. Objectives: The study was conducted to assess satisfaction, explore the influencing factors and to find the association of satisfaction with online Teaching, Learning, and Assessment (TLA) during COVID-19 pandemic among nursing students with selected socio-demographic characteristics. Materials and Methods: A quantitative research approach, total enumerative sampling technique was used to select the sample, that is, 200. Data gathered using self-structured student satisfaction questionnaire and a checklist to find the influencing factors for satisfaction with online TLA during COVID-19 pandemic. Results: Out of 200 subjects, 121 (60.5) were indecisive. Study revealed that online technology related factors, learning resources and materials, teacher learner interaction, individual factors, and teacher factors were influencing factors, out of which majority of the subjects, that is, 175 (87.5%) faced connectivity problems, 143 (71.5%) were satisfied with the arrangement of learning material in a logical and understandable manner. There was a significant association of father’s education, type of connectivity having P = 0.031 and P = 0.043 with satisfaction of online TLA. Conclusion: The study findings revealed that more than 50% of students were indecisive and online technology related factors, learning resources and materials, individual factors, teacher factors were the major influencing factors. Father’s education and type of connectivity were found to be significantly associated with satisfaction of online TLA during COVID-19 pandemic.